Periodontal Tissue Regeneration Using Syngeneic Adipose‐Derived Stromal Cells in a Mouse Model. (16th September 2016) - Lemaitre, Mathieu; Monsarrat, Paul; Blasco‐Baque, Vincent; Loubières, Pascale; Burcelin, Rémy; Casteilla, Louis; Planat‐Bénard, Valérie; Kémoun, Philippe
Abstract: Current treatment of periodontitis is still associated with a high degree of variability in clinical outcomes. Recent advances in regenerative medicine by mesenchymal cells, including adipose stromal cells (ASC) have paved the way to improved periodontal regeneration (PD) but little is known about the biological processes involved. Here, we aimed to use syngeneic ASCs for periodontal regeneration in a new, relevant, bacteria‐induced periodontitis model in mice. Periodontal defects were induced in female C57BL6/J mice by oral gavage with periodontal pathogens. We grafted 2 × 10 5 syngeneic mouse ASCs expressing green fluorescent protein (GFP) (GFP+/ASC) within a collagen vehicle in the lingual part of the first lower molar periodontium (experimental) while carrier alone was implanted in the contralateral side (control). Animals were sacrificed 0, 1, 6, and 12 weeks after treatment by GFP+/ASC or vehicle graft, and microscopic examination, immunofluorescence, and innovative bio‐informatics histomorphometry methods were used to reveal deep periodontium changes. From 1 to 6 weeks after surgery, GFP+ cells were identified in the periodontal ligament (PDL), in experimental sites only. After 12 weeks, cementum regeneration, the organization of PDL fibers, the number of PD vessels, and bone morphogenetic protein‐2 and osteopontin expression were greater in experimental sites than in controls. Specific stromal cell subsets were recruited in the newly formed tissue in ASC‐implanted periodontium only. These data suggest that ASC grafting in diseased deep periodontium, relevant to human pathology, induces a significant improvement of the PDL microenvironment, leading to a recovery of tooth‐supporting tissue homeostasis. Stem Cells Translational Medicine 2017;6:656–665